Hyponormal Toeplitz Operators on the Dirichlet Spaces - Puyu Cui; Yufeng Lu (Abstract and Applied Analysis)
We completely characterize the hyponormality of bounded Toeplitz operators with Sobolev symbols on the Dirichlet space and the harmonic Dirichlet space.